2021
DOI: 10.1097/iop.0000000000002085
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Distensible Orbital Venous-dominant Venolymphatic Malformations After Sclerotherapy Versus Embolization With Excision

Abstract: Treatment for orbital venolymphatic malformations (VLMs) commonly includes 3 major options: sclerotherapy, surgery, and embolization followed by surgical excision. Each has certain advantages, although it is not clear whether all are effective. The authors characterize the clinical course for a series of patients with distensible orbital venous-dominant VLM treated with sclerotherapy and/or embolization with excision.Methods: In this cross-sectional cohort study, patients affected by distensible orbital venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Typical management with either sclerotherapy or embolization and excision are both designed to stabilize the baseline (non-Valsalva augmented) state. 5,7 In patients with significant baseline enophthalmos this will, by design, leave the patient volume depleted. In some cases, there may be a role for leaving the glued lesion in situ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical management with either sclerotherapy or embolization and excision are both designed to stabilize the baseline (non-Valsalva augmented) state. 5,7 In patients with significant baseline enophthalmos this will, by design, leave the patient volume depleted. In some cases, there may be a role for leaving the glued lesion in situ.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasis accounts for the complexity in the presentation and can be useful in guiding management. 5 Whatever the tissue composition may be, the hemodynamic properties of orbital VMs play a critical role in identifying an appropriate management plan. 6,7 On the venous side, distensibility takes on a more central role in the orbit, as it is a nonexpansible space with a single outlet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sclerotherapy with intralesional injection of sclerosants, including ethanol, morrhuate sodium, sodium tetradecyl sulfate, OK-432 (Picibanil), doxycycline, tetracyclines, bleomycin, or pingyangmycin, is a minimally invasive and effective treatment for orbital venous malformations. 16 , 17 , 20 Nonetheless, a direct puncture with contrast injection under fluoroscopic imaging guidance is typically required to confirm both the needle location within the lesion and the flow characteristics. 1 Furthermore, all sclerosing agents cause direct endothelial injury with resultant thrombosis and fibrotic obliteration of the vascular lumen, with the exception of OK-432, which induces inflammation via cytokine release to achieve the same objective.…”
Section: Discussionmentioning
confidence: 99%
“…As OVLM lesions are often poorly demarcated, complete gross resection is challenging and there is thus a high recurrence rate after attempted primary resection 3. Recent literature has demonstrated that sclerotherapy may be ineffective for patients with distensible, venous-dominant moderate-flow OVLM due to frequent recurrence 4. OVLM recurrence rates as high as 23% postsclerotherapy and 58% postsurgical resection have been reported 5,6…”
Section: Discussionmentioning
confidence: 99%